2012
DOI: 10.2355/isijinternational.52.1394
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Analysis of the Decomposition Reaction of CH4 Injecting into Molten Slag

Abstract: Utilization of heat of slag is key technology for the reduction of CO2 emission in steel industries. While hydrogen production is important for the society of aiming to the sustainable energy system, the green hydrogen must be produced for the actual CO2 reduction.In the present study, methane gas was injected into a molten slag and hydrogen was produced through the thermal decomposition reaction. CH4 = C + 2H2Kinetic analysis was performed using an graphite crucible both with empty and slag. The rate constant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…As a product of the first-step methane decomposition reaction, the concentration of CH 3 is the second highest, and it is active enough because of the existence of the dangling bond. , Besides, radical hydrogen (H*) could promote the decomposition of CH 4 to CH 3 (detailed possible routes where CH 4 decomposes into CH 3 can be seen in the SI). ,− For other carbon species, such as CH 2 , CH, and C, although they are also active enough, their concentrations are many orders of magnitude lower than that of CH 3 (see Figure S5 and the related text in the SI). From the above analysis, we conclude that gas-phase CH 3 is the dominating species during the graphene growth on the insulating surfaces as illustrated in Figure c.…”
Section: Resultssupporting
confidence: 80%
“…As a product of the first-step methane decomposition reaction, the concentration of CH 3 is the second highest, and it is active enough because of the existence of the dangling bond. , Besides, radical hydrogen (H*) could promote the decomposition of CH 4 to CH 3 (detailed possible routes where CH 4 decomposes into CH 3 can be seen in the SI). ,− For other carbon species, such as CH 2 , CH, and C, although they are also active enough, their concentrations are many orders of magnitude lower than that of CH 3 (see Figure S5 and the related text in the SI). From the above analysis, we conclude that gas-phase CH 3 is the dominating species during the graphene growth on the insulating surfaces as illustrated in Figure c.…”
Section: Resultssupporting
confidence: 80%
“…Observing the flow rate of H 2 , found that there is high amount of H 2 in system. The study of Kashiwaya Y., and Watanabe M. reported that methane decomposition is reversible reaction in gas phase before CNTs growth 42 . Therefore, according to Le Chatelier’s principle, when the product quantity (H 2 ) increases, will prevent the dissociation of methane, resulting in fewer CNTs 43 , 44 .…”
Section: Resultsmentioning
confidence: 99%
“…Recent research has focused on enhancing hydrogen production by the direct thermocatalytic decomposition of methane to form elemental carbon and hydrogen as an attractive alternative to the conventional steam reforming process [4]. Thermodynamically, the reaction of CH4(g) → C + 2H2(g) can occur from 543°C, but kinetically, the reaction becomes dominant from 800°C without any catalyst [5]. Methane decomposition is a moderately endothermic reaction.…”
Section: Introductionmentioning
confidence: 99%